PENGGUNAAN MEDIA KARTU PERAN UNTUK MENINGKATKAN MINAT BELAJAR IPAS DI KELAS IV SD INPRES 6/80 KAWERANG KABUPATEN BONE - Sitti Jauhar; Rosmalah; Ailinyuliani (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This study is a classroom action research study aimed at increasing interest in learning Natural and Social Sciences (IPAS) in fourth-grade elementary school students through the use of role cards. The study was conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects were 23 fourth-grade students. Data collection techniques included observations of teacher and student activities during the learning process and a questionnaire on learning interest in IPAS to measure the effectiveness of the intervention. The results showed an increase in student learning interest from cycle I to cycle II. In cycle I, 9 students (39.13%) achieved the learning interest success indicator, while 14 students (60.87%) did not achieve the success indicator. After improving learning in Cycle II by optimizing the use of role cards, all 21 students (91,3%) successfully achieved the learning interest indicator. Furthermore, teacher and student activity also improved, as evidenced by the increase in the percentage of learning implementation from